2016
DOI: 10.1080/24748668.2016.11868877
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Male Handball Goalkeepers: A historical overview 1982-2012

Abstract: Abstract:In this article, an analysis of the historical evolution of the effectiveness of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
4
0
7

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 18 publications
3
4
0
7
Order By: Relevance
“…The results of the study showed that the percentage of saves was higher for shots from nine meters followed by those from the wings six meters fast-breaks seven meters and breakthroughs. These results partially coincide with those previously found by Espina-Agulló et al 4 with goalkeepers of a similar level although the classification used by these authors was different. Likewise the results also coincide with the results provided by Hansen et al 17 with a sample of goalkeepers belonging to 24 teams that participated in the 2015 world championships.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The results of the study showed that the percentage of saves was higher for shots from nine meters followed by those from the wings six meters fast-breaks seven meters and breakthroughs. These results partially coincide with those previously found by Espina-Agulló et al 4 with goalkeepers of a similar level although the classification used by these authors was different. Likewise the results also coincide with the results provided by Hansen et al 17 with a sample of goalkeepers belonging to 24 teams that participated in the 2015 world championships.…”
Section: Discussionsupporting
confidence: 91%
“…In team sports and specifically in handball, different lines of research have been opened, among which the study of competition and analysis of team performance through the use of game statistics from national and international competitions stands out [1][2][3][4][5][6][7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…En los últimos 30 años han aumentado los lanzamientos desde 9m y 6m pero con una efectividad variable debido tanto a la mejor preparación de los porteros como al scouting, elemento este utilizado por los porteros de élite analizando en imágenes los lanzamientos de los rivales en partidos anteriores (Espina-Agulló et al, 2016). La información aportada a los porteros es muy útil ya que la tendencia de todos los jugadores, es tener determinada tendencia a intentar colocar el balón casi siempre los mismos ángulos, pudiendo ser bajo largo, medio largo, alto largo, bajo corto, medio corto, alto corto, así como lanzamiento de recurso, es decir, en trayectoria parabólica, liftada de rosca.…”
Section: Discussionunclassified
“…Siguiendo con el análisis de los factores condiciones del lanzamiento, no todos dependen del lanzador. De todos ellos se destaca la oposición a la que se enfrenta (Rivilla-Garcia, Grande, Sampedro, & van den Tillaar, 2011), el papel del portero (Espina-Agulló, Pérez-Turpin, Jiménez-Olmedo, Penichet-Tomás, & Pueo, 2016), así como las características antropométricas de la defensa. Todos estos factores externos al lanzador, condicionan su respuesta de ataque y adaptación de los patrones técnicos para sobrepasar las dificultades encontradas para poder realizar un lanzamiento de calidad que permita la obtención del tanto.…”
unclassified